2017
DOI: 10.1007/s10344-017-1156-8
|View full text |Cite
|
Sign up to set email alerts
|

Admixture between released and wild game birds: a changing genetic landscape in European mallards (Anas platyrhynchos)

Abstract: Disruption of naturally evolved spatial patterns of genetic variation and local adaptations is a growing concern in wildlife management and conservation. During the last decade, releases of native taxa with potentially non-native genotypes have received increased attention. This has mostly concerned conservation programs, but releases are also widely carried out to boost harvest opportunities. The mallard, Anas platyrhynchos, is one of few terrestrial migratory vertebrates subjected to large-scale releases for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 64 publications
(91 reference statements)
4
39
0
Order By: Relevance
“…Until recently, molecular methods did not distinguish among mallards across their Holarctic distribution (Kraus et al, ). However, Söderquist et al () used genomic sequencing and reported feral European mallards not only have a distinct genetic signature, but also showed them to have a significant impact on wild European mallard stocks. Although the authors did not find the same trend in North America, they did not adequately sample east of the Mississippi River and thus likely missed the non‐western genetic signature captured here.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, molecular methods did not distinguish among mallards across their Holarctic distribution (Kraus et al, ). However, Söderquist et al () used genomic sequencing and reported feral European mallards not only have a distinct genetic signature, but also showed them to have a significant impact on wild European mallard stocks. Although the authors did not find the same trend in North America, they did not adequately sample east of the Mississippi River and thus likely missed the non‐western genetic signature captured here.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the translocation of individuals of non-local origin may lead to introgression that disrupts spatial genetic structure, alters local genetic diversity, and ultimately threatens local adaptations (e.g., Söderquist et al 2017 and references therein). Hybridisation between translocated farmed and wild individuals might also be a driver of biodiversity loss (Randi 2008;Sutherland et al 2006;Söderquist et al 2017).…”
Section: Potential Impacts Of Commercial Trade On Ball Python Populatmentioning
confidence: 99%
“…We explicitly test whether the two genetic mallard clusters in North America are due to natural (i.e., divergence within wild mallards) or artificial (i.e., anthropogenic release of domesticated game‐farm mallards) processes. The former seems unlikely as wild mallards show no discernible structure across their Holarctic distributions (Champagnon et al, ; Kraus et al, ; Söderquist et al, ), with the only genetic structure within Eurasian mallards due to hybridization with captive‐bred mallards (Söderquist et al, ). Furthermore, tracking data show that when mallards migrate between Eurasia and North America, the path used is eastward through Alaska and not westward across the Atlantic Ocean (Hupp et al, ; Lam et al, ; Shin et al, ; Yamaguchi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The former seems unlikely as wild mallards show no discernible structure across their Holarctic distributions (Champagnon et al, 2013;Kraus et al, 2011;Söderquist et al, 2017), with the only genetic structure within Eurasian mallards due to hybridization with captive-bred mallards (Söderquist et al, 2017). Furthermore, tracking data show that when mallards migrate between Eurasia K E Y W O R D S ancient DNA, biological collections, hybridization, introgression, population genetics, speciation and North America, the path used is eastward through Alaska and not westward across the Atlantic Ocean Lam et al, 2012;Shin et al, 2015;Yamaguchi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%